GREEN HUMAN RESOURCE MANAGEMENT DAN EMPLOYER BRANDING: PERAN MEDIASI ORGANIZATIONAL IDENTIFICATION SERTA MODERASI NILAI LINGKUNGAN INDIVIDU PADA SEKTOR MANUFAKTUR DAN JASA - Bambang Sumardi; Ellin Herlina; Hartanto Halim; Yeyet Daryati; Freddy FM Pandiangan; Nur Alia Sumanti (The Asia Pacific Journal Of Management Studies, 2026)
This study aims to examine how Green Human Resource Management (Green HRM) practices influence employer branding and organizational commitment through organizational identification, and how individual environmental values strengthen these relationships. Drawing on social identity theory and signaling theory, the study argues that environmentally oriented HRM practices not only shape positive perceptions of the organization but also foster greater pride, attachment, and stronger identification among employees. The study is designed using a cross-sector quantitative approach in manufacturing and service organizations, employing SEM-PLS analysis to test direct, mediation, and moderation relationships. The contribution of this research lies in the integration of Green HRM, employer branding, and organizational commitment into a single conceptual model that explains the psychological mechanisms and boundary conditions of the effectiveness of sustainable HRM practices. The findings are expected to provide strategic implications for organizations seeking to build a strong employer image while retaining employees through HRM practices aligned with sustainability.